Pengaruh Event Terhadap Citra Merek Majalah Femina - Gea Wahyu Syahrinnisa; Ma'mun Sarma (Jurnal Manajemen dan Organisasi, 2019)
The print media industry dealing with large business competition due to the rise of online media. Online media provides convenience to access information. Print media utilizes online media as an information provider and a media promotion. Femina is one of the Indonesia print media merging between print and online media. Femina do marketing communication, one of them is event. This study aims to (1) identify the Femina event participants, (2) analyze the participant’s perceptions regarding the conduct of Femina’s event, and (3) analyze the effect of the event to the brand image of Femina Magazine. Sampling was employed by quota sampling. Respondents were 41 people which are collected when the event was performed: Healthy Action with Mama Lime and Femina, and Enchaunter L'amour Extraordinare. Data processing and analysis using Structural Equation Models (SEM) with software SmartPLS 2.0. The results showed that the majority of respondents’ characteristics in accordance with Femina reader segmentation and perception of the participants’ event are good. The uniqueness, atmosphere and service of the event are significant to the brand image of Femina Magazine.